Chemical Characteristics of Surface Water of Sumpil River and Groundwater on its Surroundings - Mukhlis Arief Irvandi; Hari Siswoyo; Dasapta Erwin Irawan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The objective of this study was to know the chemical characteristics of surface water in a segment of Sumpil River and the groundwater on its surrounding. The location of this study was in 3 cross sections, consisting of 1 well on the right of the Sumpil River, 1 well on the left of the Sumpil River flow, and 1 point on the Sumpil River flow. The chemical characteristics of the water were determined by the concentrations of cations and anions in the water sample using the Piper Trilinear Diagram with the GW Chart 1.30 computer program. Based on the results of the study, it was shown that the chemical characteristics of the Sumpil River water and the groundwater at the location of this study were the same, where all water samples had an alkaline earth metals content over the alkali content (zone 1), had a strong acidic content exceeding the weak acidic content (zone 4), have a balanced cation and anion pairs, none of which exceed 50% (zone 9), and shown that all of the water in the location of this study were fresh water.